INTERIOR AS EXTERIOR AND LANDSCAPE CONNECTOR - Ika Yuni Purnama; Sri Fariyanti Pane (Universitas Trisakti, 2021)
Interior is a space that is related to the outer and surrounding spaces. This space is also very close to the needs and complexities of human life. Now, the meaning and practice of interior design is not limited to fill or decoration within the physical boundaries that have been formed by architecture. This writing aims to change the general perception and view of interior science, namely as a science that bridges the inner space (interior) with the outer space (architecture and landscape) which also connects humans and their environment. This paper is the result of qualitative research using literature methods and case studies. The results of the discussion refer to several examples of interior and exterior processing (architecture and landscapes) that can be used in design practice with interior concepts as a liaison, namely by physically and conceptually manipulating space, the scope of interior design becomes a science that has a very important role to fulfill human needs. physically and psychologically.